Basalt ultra-high performance concrete and preparation method thereof

By replacing traditional materials with basalt sand, powder and fiber, basalt ultra-high performance concrete with high corrosion resistance and chemical stability is prepared, which solves the problems of easy erosion and high cost of steel fibers in the prior art, and realizes the Performance improvement and cost reduction effects.

CN119390413APending Publication Date: 2025-02-07GUANGXI AIRPORT MANAGEMENT GRP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411531829.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete uses steel fibers that are easily eroded by chloride ions, have poor durability, and have high cost of steel, making it difficult to be used in coastal airports, expressways, docks and ship locks.

Method used

Basalt sand, basalt powder and basalt fibers are used to replace traditional quartz sand, quartz powder and steel fibers. By adjusting the mix ratio and preparation methods of raw materials, basalt ultra-high performance concrete with high corrosion resistance and chemical stability is prepared.

Benefits of technology

It has achieved the performance improvement of ultra-high performance concrete, reduced production costs, improved the durability and corrosion resistance of materials, and is suitable for engineering applications in coastal environments and other environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of basalt concrete, in particular to basalt ultra-high performance concrete and a preparation method thereof, the preparation method comprises a raw material screening method and a preparation method, and the raw material screening comprises the steps of (1) selecting ultra-high performance concrete water, (2) selecting a cementing material, (3) selecting aggregate and (4) selecting fiber. The preparation method comprises the following steps: (1) the use amount of water should meet the design specification of the ultra-high performance concrete, and the water-binder ratio should be controlled within 0.25; and (2) according to the particle sizes of the cementing material and the sand, the dosage of each component is calculated on the basis of the closest packing theory, and the sand-cement ratio is controlled within 1.1-1.4. By adopting the method, in-situ utilization of the raw materials of the ultra-high-performance concrete can be realized in volcanic diagenetic regions, and design, preparation and application of the basalt ultra-high-performance concrete can be realized in practical engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of basalt concrete, and in particular to a basalt ultra-high performance concrete and a preparation method thereof, which are suitable for screening and preparing ultra-high performance concrete structures made of basalt materials such as airport runways, highways, docks, waterways and ship locks. Background Art

[0002] Basalt is a basic extrusive rock. It is a dense or foamy rock formed by the magma erupted from the volcano and solidified after cooling on the surface. It belongs to igneous rock. The use of basalt to prepare concrete materials has obvious location advantages in southern my country, which can minimize the impact of ultra-high performance concrete (UHPC) on the environment. Therefore, the use of basalt to prepare ultra-high performance concrete has the advantages of location, low price and environmental protection. Using basalt materials to replace the original materials can achieve the original ultra-high performance concrete performance or improve it to a certain extent.

[0003] Since existing UHPC mostly uses steel fibers, which are easily corroded by chloride ions, the material fails and has poor durability. The cost of steel is relatively high, and the price of steel fibers is relatively expensive. The corrosion protection mainly relies on copper and zinc plating on the fiber surface, which is not conducive to its application in coastal airports, highways, docks and ship locks. Basalt sand (BS), basalt powder (BP) and basalt fiber (BF) can be used to replace traditional quartz sand, quartz powder and steel fiber in UHPC. The raw materials for the production of aggregates and fibers come from the rocks mined along the project. If they meet the standards, they can be made into the required BS, BP and BF, so the cost is relatively low, and its price is more favorable than other reinforcing materials. At the same time, basalt fiber has high corrosion resistance and chemical stability and good corrosion resistance. Summary of the invention

[0004] One of the purposes of the present invention is to provide a basalt ultra-high performance concrete. Using basalt materials to replace original materials can achieve the performance of the original ultra-high performance concrete, and the performance is improved to a certain extent. It also has the advantages of location, low price and environmental protection.

[0005] The second object of the present invention is to provide a method for preparing basalt ultra-high performance concrete, using basalt sand (BS), basalt powder (BP) and basalt fiber (BF) to replace traditional quartz sand, quartz powder and steel fiber in ultra-high performance concrete. The raw materials for the production of aggregates and fibers come from the rocks mined along the project that meet the standards and can be made into the required BS, BP and BF, so the cost is relatively low, and its price is more favorable than other reinforcing materials. At the same time, basalt fiber has the characteristics of high corrosion resistance and good chemical stability and anti-erosion effect.

[0006] The present invention achieves the above object by adopting the following technical solution: A basalt ultra-high performance concrete, wherein the mass fractions of each component per cubic meter are:

[0007]

[0008] Steel fiber / macro basalt fiber 0-39 parts

[0009] Microfilament basalt fiber 0~40 parts

[0010] Water reducing agent 0-35 parts.

[0011] The preparation method of basalt ultra-high performance concrete includes two parts: raw material screening and preparation method.

[0012] Raw material screening part:

[0013] (1) Selection of water for ultra-high performance concrete: Purified water is preferred, with a pH value of 6.5 to 8.5 for urban water supply and a total hardness (calcium carbonate) of ≤350 mg / L;

[0014] (2) Selection of cementitious materials: cement with a P·O 42.5 or higher grade is selected, preferably P·O 52.5 cement, and mineral admixtures include high-quality silica fume and fly ash;

[0015] (3) Aggregate selection: basalt matrix is ​​selected, and the basalt matrix is ​​crushed and ground into basalt sand and basalt powder;

[0016] (4) Fiber selection: steel fiber, macroscopic basalt fiber or microfilament basalt fiber, or a composite fiber of steel fiber, macroscopic basalt fiber and microfilament basalt fiber;

[0017] The high-quality silica ash has a silicon dioxide content greater than or equal to 95% and an average particle size of 0.2 μm; the fly ash is F-type low-calcium fly ash with a CaO content less than 10%; the basalt sand is obtained by crushing rocks mined along the project, and basalt sand with gradations of 10-20 mesh, 20-40 mesh and 40-80 mesh is selected; the basalt powder is selected to pass through a 300-mesh sieve with a particle size of 48 microns; steel fiber, macro basalt fiber or micro basalt fiber is selected, the steel fiber and macro basalt fiber are selected from macro fibers with a diameter of 200 μm, a length of 12 mm, an elastic modulus of 200 GPa and a tensile strength of 3000 MPa, and the micro basalt fiber is selected from short fibers with a diameter of 13-17 μm, a length of 12 mm, an elastic modulus of 100 Gpa and a tensile strength of 0.41 N / tex; the water reducer is a polycarboxylic acid high-efficiency water reducer or other high-efficiency water reducers, and the mother liquor has a water reduction rate of ≥35%.

[0018] Preparation method part:

[0019] (1) The amount of water used should meet the design specifications for ultra-high performance concrete, and the water-cement ratio should be controlled within 0.25, which should be appropriately adjusted according to the fluidity of ultra-high performance concrete;

[0020] (2) According to the particle size of cementitious materials and sand, the amount of each component is calculated based on the closest packing theory, and the sand-binder ratio is controlled within 1.1 to 1.4. The amount of each component calculated based on the closest packing theory and properly adjusted is 2:2:1 for the mass ratio of 10-20 mesh, 20-40 mesh and 40-80 mesh grading machine-made basalt sand; the water-binder ratio is controlled at 0.18-0.2; the volume fraction of fiber addition is 2%; and the water reducer is added at 3% of the mass fraction of the cementitious material;

[0021] (3) First, stir the three kinds of basalt sand and cementitious materials at a low speed according to the proportion, so that the fine aggregate and cementitious materials are evenly mixed, and then add the polycarboxylic acid high-efficiency water-reducing agent mother liquor and purified water. When the water-reducing agent takes effect and the fluidity of the stirred mortar is good, slowly and evenly add the fiber, stir for 3-5 minutes to fully mix, and then stir at a high speed to fully mix. Finally, pour the mixed slurry into a test mold and measure the fluidity of the mixture. Keep its fluidity at >170±10mm, and the basalt ultra-high performance concrete product is obtained.

[0022] The specific steps are as follows:

[0023] 1) Add the cementitious material and fine aggregate into the mixer and dry mix at low speed for 30 seconds to make the dry materials evenly mixed;

[0024] 2) Add water and SP and stir at low speed for 30 seconds to mix the dry material with water and stimulate SP to form a slurry;

[0025] 3) Slowly add fibers several times and stir at low speed for 60 seconds to evenly mix the fibers and slurry to form a UHPC mixture;

[0026] 4) Stir the mixture at high speed for 30 seconds, let it stand for 90 seconds, and then stir at high speed for 60 seconds.

[0027] 5) After stirring, the mixture is tested for fluidity and poured into a 40mm×40mm×160mm mold. The mixture and the mold are placed in a standard (temperature of 20°C±2°C, relative humidity of 97%±2%) curing box for 24 hours.

[0028] 6) The UHPC specimens were demoulded and placed in a rapid curing box for high-temperature steam curing. After curing for 1 day and 3 days, they were transferred to a standard curing room for curing for 7 days and 28 days. The curing conditions are convenient for implementation in actual engineering.

[0029] The mechanical properties of basalt ultra-high performance concrete with a fluidity of 160-220mm are as follows: the strength reaches 50%, 70%, and 95% of the standard strength at the ages of 3d, 7d, and 28d, respectively; the standard flexural strength at the 28d curing age is 24Mpa and the compressive strength is 120Mpa.

[0030] The finished product curing standard adopts the method of placing the ultra-high performance concrete specimen in a curing box with a temperature of 90°C ± 1°C and a relative humidity of 97% ± 2% for high-temperature steam curing for 1 day and 3 days.

[0031] The polycarboxylic acid high-efficiency water reducing agent or other high-efficiency water reducing agent is added in an amount of 3% of the mass of the cementitious material, and the water reduction rate is higher than 35%.

[0032] The technical effects achieved by the present invention are as follows:

[0033] 1. Under the premise of ensuring the performance of ultra-high performance concrete in all aspects, the present invention uses basalt sand instead of quartz sand, basalt powder instead of quartz powder, and basalt fiber instead of steel fiber, thereby reducing the production cost of ultra-high performance concrete.

[0034] 2. Steel fiber has poor durability and is easily corroded. Anti-corrosion usually adopts copper plating and galvanizing, which are expensive. Basalt fiber has strong anti-corrosion ability, and the wide distribution of basalt can effectively reduce engineering costs.

[0035] 3. Basalt sand is used instead of quartz sand. Its compressive strength is about 2.5 to 4 times that of ordinary concrete, reaching or exceeding the UHPC compressive strength requirement of 120MPa.

[0036] 4. Basalt sand is made of two particle size gradations of 10-20 mesh, 20-40 mesh and 40-80 mesh sieves and is evenly mixed in a ratio of 2:2:1, which can achieve good particle grading and minimize the negative impact on the mechanical properties of UHPC.

[0037] Technical principle:

[0038] The present invention adopts basalt fiber to replace part or all of the steel fiber in ultra-high performance concrete. Basalt fiber is a new composite material made of natural basalt as raw material, melted at 1400-1500°C, stretched into fibers, and made of these fibers as reinforcement. It has high corrosion resistance and chemical stability, and strong chemical stability in alkaline solution. It is widely used in concrete structures such as bridges, tunnels, dams, as well as asphalt concrete pavements, aircraft landing strips and other important building structures that are often exposed to high humidity, acid, alkali, and salt media.

[0039] Silica fume has significant volcanic ash activity. It can participate in secondary hydration to generate secondary hydration product CSH to strengthen the UHPC matrix. Basalt powder can effectively reduce the porosity in ultra-high performance concrete by utilizing its filling effect. It can also participate in secondary hydration reaction under high-temperature steam curing conditions to strengthen the UHPC matrix and improve the mechanical properties of ultra-high performance concrete.

[0040] The present invention uses basalt fiber (macro / micro filament) instead of steel fiber, basalt sand instead of quartz sand, and basalt powder instead of quartz powder. The production cost of ultra-high performance concrete can be effectively reduced with little or no reduction in strength, and the durability of UHPC can be significantly improved.

[0041] The high-temperature steam curing method adopted by the present invention can be implemented in laboratories and engineering practices. Standard curing is subsequently used to replace long-term high-temperature steam curing. The curing method is simple, the curing cost is relatively low, and it is convenient for actual engineering application. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figures 1 to 5 It is a schematic diagram of the fluidity and strength test results of the basalt ultra-high performance concrete prepared in Examples 1 to 5.

[0043] Figure 6 It is a schematic diagram of the fluidity test results of the ultra-high performance concrete in the control group. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described in detail below through examples.

[0045] Example 1

[0046] This embodiment is an example of the basalt ultra-high performance concrete and its preparation method according to the present invention.

[0047] The raw material ratio (based on 1m 3 The amount of concrete materials) and properties are as follows:

[0048] The cement is P·O52.5 cement with a specific surface area of ​​400m 2 / kg, 28d compressive strength is 58Mpa; Silica fume: SiO2 content> 95%, specific surface area is 20000m 2 / kg, density is 625kg / m 3 .

[0049] The basalt sand is made by uniformly mixing two specifications of sand, 10-20 mesh, 20-40 mesh and 40-80 mesh, in a mass ratio of 2:2:1.

[0050] Water reducing agent: polycarboxylic acid high-efficiency water reducing agent or other high-efficiency water reducing agent, with a water reducing rate greater than 35%.

[0051] Water: Purified water is preferred, with a pH value of 6.5 to 8.5 for urban water supply and a total hardness (measured as calcium carbonate) ≤350 mg / L.

[0052] Basalt fiber: The volume content of short fibers with a diameter of 17 nm, a length of 6 mm, an elastic modulus of 100 Gpa, and a tensile strength of 0.41 N / tex is 2%.

[0053] The raw material mix ratio of basalt ultra-high performance concrete prepared in this experimental example (1m 3 The amount of each raw material used in ultra-high performance concrete is shown in Table 1:

[0054] Table 1 Raw material mix design of basalt ultra-high performance concrete (kg / m 3 )

[0055]

[0056] The method for preparing the basalt ultra-high performance concrete comprises the following steps:

[0057] Step 1: Weigh three kinds of basalt sand and 300-mesh basalt powder according to the mix ratio, pour into the mortar mixer and stir slowly and evenly.

[0058] Step 2: Weigh cement and silica fume according to the mix ratio, pour into the mortar mixer and mix slowly and evenly.

[0059] Step 3: Weigh polycarboxylic acid or other high-efficiency water reducer according to the mix ratio and mix with pure water, then pour into a mixer and stir for 3 minutes until the ultra-high performance concrete has good fluidity.

[0060] Step 4: Add basalt fiber evenly according to the mixing ratio and stir quickly for 2 minutes until uniform.

[0061] Step 5: Determine the fluidity of the mixed slurry according to the standard, pour it into a 40mm×40mm×160mm triple test mold, vibrate 60 times, and place it in a standard curing box with the mold to cure for one day.

[0062] Step 6: De-mould the UHPC specimens and place them in a rapid curing box for high-temperature steam curing (temperature 90°C ± 1°C, relative humidity 97% ± 2%) for 1d and 3d. After the high-temperature steam curing is completed, transfer them to a standard curing room for curing for 7d and 28d respectively.

[0063] Step 7: Performance test of basalt ultra-high performance concrete described in this experiment (as shown in Table 1):

[0064] According to GB / T17671-2021 Cement Mortar Strength Test Method (ISO Method), the fluidity of the invented basalt ultra-high performance concrete is 173mm, the prism compressive strength is 53.6MPa at 3d, 84.3MPa at 7d, and 124.7MPa at 28d. The flexural strength is 14.4MPa at 3d, 20.3MPa at 7d, and 24.6MPa at 28d.

[0065] Example 2

[0066] This embodiment is another example of the basalt ultra-high performance concrete and its preparation method according to the present invention. The raw material requirements and preparation method are the same as those in Example 1.

[0067] The raw material mix ratio of basalt ultra-high performance concrete prepared in this experimental example (1m 3 The amount of each raw material used in ultra-high performance concrete is shown in Table 2:

[0068] Table 2 Raw material mix design of basalt ultra-high performance concrete (kg / m 3 )

[0069]

[0070] Example 3

[0071] This embodiment is another example of the basalt ultra-high performance concrete and its preparation method according to the present invention. The raw material requirements and preparation method are the same as those in Example 1.

[0072] The raw material mix ratio of basalt ultra-high performance concrete prepared in this experimental example (1m 3 The amount of each raw material used in ultra-high performance concrete is shown in Table 3:

[0073] Table 3 Raw material mix design of basalt ultra-high performance concrete (kg / m 3 )

[0074]

[0075] Example 4

[0076] This embodiment is another example of the basalt ultra-high performance concrete and its preparation method according to the present invention. The raw material requirements and preparation method are the same as those in Example 1.

[0077] The raw material mix ratio of basalt ultra-high performance concrete prepared in this experimental example (1m 3 The amount of each raw material used in ultra-high performance concrete is shown in Table 4:

[0078] Table 4 Raw material mix design of basalt ultra-high performance concrete (kg / m 3 )

[0079]

[0080] Example 5

[0081] This embodiment is the fifth example of the basalt ultra-high performance concrete and the preparation method thereof of the present invention. The raw material requirements and the preparation method are the same as those of Embodiment 1.

[0082] The raw material mix ratio of basalt ultra-high performance concrete prepared in this experimental example (1m 3 The amount of each raw material used in ultra-high performance concrete is shown in Table 5:

[0083] Table 5 Raw material mix design of basalt ultra-high performance concrete (kg / m 3 )

[0084]

[0085] Comparative Example

[0086] Table 6 shows the raw material mix design of ultra-high performance concrete in the control group. No basalt material is used. Quartz sand, quartz powder and steel fiber correspond to basalt sand, basalt powder and mixed steel fiber and basalt fiber in the raw material mix design of basalt ultra-high performance concrete, respectively.

[0087] Table 6 Raw material mix design of ultra-high performance concrete for the control group (kg / m 3 )

[0088]

[0089] Figure 6 It is the fluidity test result of the ultra-high performance concrete in the control group.

[0090] Table 7 shows the test results of flexural strength and compressive strength of the basalt ultra-high performance concrete prepared in Examples 1 to 5 and the control group.

[0091]

[0092] From the test results in Table 7, it can be seen that the use of basalt materials to prepare ultra-high performance concrete significantly enhances the strength of ultra-high performance concrete without affecting the fluidity of ultra-high performance concrete, and has a significant toughening effect. The replacement of steel fiber with basalt fiber also reduces the cost expenditure of ultra-high performance concrete on fiber use. The improvement comparison between Example 3 with the best performance and the control group is shown in Table 8, and the improvement is significant.

[0093] Table 8 Comparison between Example 3 and Control Group

[0094]

[0095] It should be understood that the above embodiments are only descriptions of preferred implementation schemes and do not constitute a limitation on the protection scope of the present invention. Any replacement or modification made by a person skilled in the art without departing from the protection scope of the claims of the present invention shall fall within the protection scope of the present invention. Any part not elaborated in detail in the present invention belongs to the prior art.

Claims

1. A basalt ultra-high performance concrete, characterized in that: The mass fraction of each component per cubic meter is: 782-799 parts of cement, wherein the cement is P·O 42.5 or P·O 52.5; Silica fume 167-171 parts, the silica fume is selected from high-quality silica fume with a silicon dioxide content greater than or equal to 95% and an average particle size of 0.2μm; 167-171 parts of fly ash, wherein the fly ash is F-type low-calcium fly ash, wherein the CaO content is less than 10%; 201-206 parts of water, which is purified water or city water with a pH value of 6.5-8.5; 10-20 mesh basalt sand 393-402 parts; 20-40 mesh basalt sand 393-402 parts; 196-201 parts of 40-80 mesh basalt sand; The basalt sand is obtained by crushing the rocks mined along the project, and the basalt sand with grading of 10-20 mesh, 20-40 mesh and 40-80 mesh is selected; 268-274 parts of 300-mesh basalt powder, wherein the basalt powder is sieved through a 300-mesh sieve and has a particle size of 48 microns; 39 to 116 parts of steel fiber / macro basalt fiber, wherein the macro basalt fiber is selected to have a diameter of 200 μm, a length of 12 mm, an elastic modulus of 200 GPa, and a tensile strength of 3000 MPa; 13 to 40 parts of microfilament basalt fiber, wherein the microfilament basalt fiber is short fiber with a diameter of 13 to 17 μm, a length of 12 mm, an elastic modulus of 100 GPa, and a tensile strength of 0.41 N / tex; 33-35 parts of water reducing agent, the water reducing agent adopts polycarboxylic acid high-efficiency water reducing agent, and the mother liquor with water reduction rate ≥35%.

2. The basalt ultra-high performance concrete according to claim 1, characterized in that: The mass fraction of each component per cubic meter is: (kg / m 3 ) Water-cement ratio 0.18; Cement 782-799; Silica fume 167-171; Fly ash 167-171; Water 201-206; 10-20 mesh sand 393~402; 20-40 mesh sand 393~402; 40-80 mesh sand 196~201; Basalt powder 268-274; Macroscopic basalt fibers 39-116; Microfilament basalt fiber 13-40; Water reducing agent 33~35.

3. The method for preparing basalt ultra-high performance concrete according to claim 1, characterized in that: It includes two parts: raw material screening and preparation method. Raw material screening part: (1) Select water for ultra-high performance concrete: pure water or city water with a pH value of 6.5 to 8.5, and total hardness as calcium carbonate ≤ 350 mg / L; (2) Selection of cementitious materials: cement with a P·O 42.5 or P·O 52.5 grade is selected, and silica fume and fly ash are selected as mineral admixtures; (3) Aggregate selection: basalt matrix is ​​selected, and the basalt matrix is ​​crushed and ground into basalt sand and basalt powder; (4) Fiber selection: steel fiber, macroscopic basalt fiber or microfilament basalt fiber, or a composite fiber of steel fiber, macroscopic basalt fiber and microfilament basalt fiber; Preparation method part: (1) The preparation process meets the requirements of GB / T 41054-2021 "Technical Conditions for High Performance Concrete" and JGJ / T 221-2010 "Technical Specifications for Application of Fiber Concrete"; (2) The water-binder ratio is controlled within 0.25, and is appropriately adjusted according to the fluidity of ultra-high performance concrete, and the water reducer is reasonably used within the controllable range; (3) According to the particle size of cementitious materials and sand, the amount of each component is calculated based on the closest packing theory, and the sand-cement ratio is controlled within 1.1 to 1.4; (4) First, stir the three kinds of basalt sand and cementitious materials at a low speed according to the proportion, so that the fine aggregate and cementitious materials are evenly mixed, and then add the polycarboxylic acid high-efficiency water-reducing agent mother liquor and purified water. When the water-reducing agent takes effect and the fluidity of the stirred mortar is good, slowly and evenly add the fiber, stir for 3-5 minutes to fully mix, and then stir at a high speed to fully mix. Finally, pour the mixed slurry into a test mold and measure the fluidity of the mixture. Keep its fluidity at >170±10mm, and the basalt ultra-high performance concrete product is obtained.

4. The method for preparing basalt ultra-high performance concrete according to claim 3, characterized in that: The specific steps of the preparation method are as follows: 1) Add cementitious materials and fine aggregate into a mixer and dry mix at low speed for 30 seconds to make the dry materials evenly mixed; 2) Add water and SP and stir at low speed for 30 seconds to mix the dry material with water and stimulate SP to form a slurry; 3) Slowly add fibers several times and stir at low speed for 60 seconds to evenly mix the fibers and slurry to form a UHPC mixture; 4) Stir the mixture at high speed for 30 seconds, let it stand for 90 seconds, and then stir at high speed for 60 seconds; 5) After stirring, the mixture is tested for fluidity and poured into a 40mm×40mm×160mm mold. The mixture and the mold are placed in a standard curing box with a temperature of 20℃±2℃ and a relative humidity of 97%±2% for 24 hours. 6) The ultra-high performance concrete specimens were demoulded and placed in a rapid curing box for high-temperature steam curing. After curing for 1 day and 3 days, they were transferred to a standard curing room for curing until 7 days and 28 days.

5. The method for preparing basalt ultra-high performance concrete according to claim 3, characterized in that: The dosage of each component calculated based on the closest packing theory is 10-20 mesh, 20-40 mesh and 40-80 mesh grading, the mass ratio of the regulated mechanism basalt sand is 2:2:1; the water-cement ratio is controlled at 0.18-0.2; the volume fraction of the fiber addition is 2%; and the water reducer is added at 0-3% of the mass fraction of the cementitious material.

6. The method for preparing basalt ultra-high performance concrete according to claim 3, characterized in that: The mechanical properties of basalt ultra-high performance concrete with a fluidity of 160-220mm are as follows: the strength reaches 50%, 70%, and 95% of the standard strength at the ages of 3d, 7d, and 28d, respectively; the standard flexural strength at the 28d curing age is 24Mpa and the compressive strength is 120Mpa.

7. The method for preparing basalt ultra-high performance concrete according to claim 3, characterized in that: The finished product curing standard is to place the ultra-high performance concrete specimens in a curing box with a temperature of 90℃±1℃ and a relative humidity of 97%±2% for high-temperature steam curing for 1d and 3d.

Citation Information

Cited By

  • Modified ultrafine fly ash, UHPC, preparation method and application

    CN121717568A

  • Modified ultra-fine fly ash, uhcp, and preparation method and application thereof

    CN121717568B